2013
DOI: 10.1530/eje-12-0782
|View full text |Cite
|
Sign up to set email alerts
|

High urinary ACE2 concentrations are associated with severity of glucose intolerance and microalbuminuria

Abstract: Our data suggest that the urinary ACE2 level is closely associated with T2DM and is an independent risk factor for microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 47 publications
6
48
1
Order By: Relevance
“…A majority of studies, except the one from Ye M, have confirmed that tubular ACE2 decreased significantly in diabetic patients and animal models [7,8,9]. On the other hand, UACE2 excretion significantly increased in uncomplicated type 1 diabetic patients, insulin-resistant subjects, CKD patients and renal transplant recipients, indicating it might be a potential marker for diabetes and kidney disease [13,14,15,23]. Consistent with these studies, we showed that UACE2/Cr levels were much higher in type 2 DN patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of studies, except the one from Ye M, have confirmed that tubular ACE2 decreased significantly in diabetic patients and animal models [7,8,9]. On the other hand, UACE2 excretion significantly increased in uncomplicated type 1 diabetic patients, insulin-resistant subjects, CKD patients and renal transplant recipients, indicating it might be a potential marker for diabetes and kidney disease [13,14,15,23]. Consistent with these studies, we showed that UACE2/Cr levels were much higher in type 2 DN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, soluble ACE2 in urine, which is most likely due to proteolytic shedding of its ectodomain from cells along the nephron, has been detected in several clinical and experimental studies [13,14,15,16,17]. It was reported that urinary ACE2 (UACE2) levels were significantly increased in patients with chronic kidney disease (CKD) and in renal transplant recipients compared with healthy subjects [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not known whether it is similarly protective in humans, ACE2 is detectable in human urine (Park et al 2013) and, as determined using enzyme-linked immunosorbent assay (ELISA), urinary ACE2 protein levels are found to be higher in patients with CKD, as well as in renal-transplant patients with diabetes (Mizuiri et al 2011;Xiao et al 2012). In patients with type 2 diabetes (T2D), Park et al have further demonstrated that urinary ACE2 is increased and independently associated with microalbuminuria (Park et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with type 2 diabetes (T2D), Park et al have further demonstrated that urinary ACE2 is increased and independently associated with microalbuminuria (Park et al 2013).…”
Section: Introductionmentioning
confidence: 99%